Radiological and Clinical Factors Predicting the Facial Nerve Outcome following Retrosigmoid Approach for Large Vestibular Schwannomas (VSs) - Sharma, Mayur; Sonig, Ashish; Ambekar, Sudheer; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective The aim of our study was to identify the radiological and clinical factors that predict postoperative facial nerve outcome following retrosigmoid approach for large vestibular schwannomas (VSs).Methods A total of 72 patients with large (≥ 3 cm) vestibular schwannomas was included in this retrospective study. Various parameters evaluated were age, gender, clinical presentation, tumor diameter in three planes, intrameatal extension, and pattern of growth.Results Age of the patient and presenting symptoms such as headache, ataxia, or preoperative facial nerve dysfunction correlated with poorer facial nerve outcome (p < 0.05). Patients with larger tumor volumes and extrameatal growth experienced a worse outcome (p < 0.05). Anterior and caudal extension (p = 0.001) correlated with poorer outcome, as well. Intrameatal extension and bony changes of the internal acoustic meatus did not correlate with the outcome (p > 0.05). Of the various examined factors, preoperative facial nerve function independently predicted postoperative facial nerve outcome.Conclusion Our study suggests that young patients with small tumor volume and normal facial nerve function at presentation are more likely to experience a good postoperative facial nerve outcome. These clinical and radiological parameters can be used to predict facial nerve outcome prior to surgery.
Keywords: vestibular schwannoma; facial nerve; outcome; predicting factors